A jigsaw approach to engaging STEM education for learning and teaching programming / Farizuwana Akma Zulkifle - Zulkifle, Farizuwana Akma (Universiti Teknologi MARA, Negeri Sembilan, 2024)
1. Innovation Question: Considering students ' diverse personality traits and gamer types, how can we leverage gamification to enhance engagement, motivation, and learning outcomes in teaching and learning programming within STEM education? 2. Insights Gamification in education has shown potential to increase motivation, engagement, and learning outcomes. Effects of gamification vary based on students' personality traits and gamer types. Limited research on how different gamification elements impact engagement in programming education. 3. Opportunity Develop a gamified approach to teaching and learning programming within STEM education that caters to individual student preferences and enhances learning outcomes: Explore a variety of game design elements suitable for teaching programming concepts effectively. Tailor the gamified approach to accommodate different learning styles and preferences. Integrate hands-on coding projects and challenges to reinforce programming skills. 4. a. Prototype Create a prototype of the gamified programming education platform. Design sample programming activities with gamification elements. Develop a user feedback system to gather insights on engagement and learning effectiveness. b. Experiments Test the prototype with a group of students learning programming within STEM education. Collect feedback on the gamification elements, user experience, and learning outcomes Conduct assessments to measure the impact of gamification on student engagement and programming proficiency. 5. By incorporating tailored game design elements, personalised learning experiences, and hands-oncoding projects, we aim to enhance student engagement, motivation, and learning outcomes. Our approach considers individual student preferences, personality traits, and gamer types tocreate a dynamic and effective learning environment that fosters programming skills and creativity. With a strong emphasis on research-based design and user feedback, Gamification: A Jigsaw Approach to Engaging STEM Education for Learning and Teaching Programming is poised to transform programming education and empower students to succeed in STEM fields.